Incidence, characteristics and risk factors for household and neighbourhood injury among young children in semiurban Ghana: a population-based household survey. (9th June 2014) - Gyedu, A; Nakua, E K; Otupiri, E; Mock, C; Donkor, P; Ebel, B
Abstract : Background: There are few population-based studies on household child injury in African countries. Objectives: To determine the incidence, characteristics and risk factors of household and neighbourhood injury among children in semiurban communities in Kumasi, Ghana. Methods: We conducted a cross-sectional population-weighted survey of 200 randomly selected caregivers of children under 18, representing 6801 households. Caregivers were interviewed about moderate to severe childhood injuries occurring within the past 6 months, for which the child staying home from school or activity, and/or required medical care. Multivariable logistic regression was used to identify factors associated with injury risk. Results: Annual injury incidence was 593.5 injuries per 1000 children. Common causes of injury were falls (315.7 injuries per 1000 children), followed by cuts/lacerations and burns. Most injuries (93.8%) were of moderate severity. Children whose caregivers were hourly workers (AOR=1.97; 95% CI 1.06 to 3.68) had increased odds of sustaining an injury compared to those of unemployed caregivers. Girls had decreased odds of injury (AOR=0.59; 95% CI 0.39 to 0.91). Cooking outdoors (AOR=0.45; 95% CI 0.27 to 0.76) and presence of cabinet/cupboards (AOR=0.41; 95% CI 0.24 to 0.70) in the house were protective. Among children under 5 years of age, living in uncompleted accommodation was associated with higher odds of injury compared with living in a rented single room (AOR=3.67; 95% CI 1.17 to 11.48). Conclusions: The incidence of household and neighbourhood child injury is high in semiurban Kumasi. We identified several novel injury risk factors (hourly work, younger children) and protective factors (cooking outdoors, presence of cabinet/cupboards). These data may identify priorities for household injury prevention.